Effect of synthesis procedure on the structure and properties of palladium/polycarbonate nanocomposites - Valmikanathan, O. P.; Ostroverkhova, O.; Mulla, Imtiaz S.; Vijayamohanan, K.; Atre, S. V. (Polymer, 2008)
In this paper, we compare two procedures for the synthesis of palladium (Pd)/polycarbonate (PC) nanocomposites as well as their morphological, optical, thermal and electrical properties. Pd nanoclusters were produced by the reduction of palladium chloride using a variation of Brust's method. Discrete I'd nanoclusters of similar to 15 nm size were formed in the absence of PC in the reaction mixture (ex situ method) while agglomeration of Pd nanoclusters was noticed in the presence of PC in the reaction mixture (in situ method). Fourier transform infrared spectroscopy (FTIR) suggests nanoparticle-polymer interactions and polymer conformational changes in the in situ nanocomposite films. Even after having the same Pd content, the ex situ nanocomposites films were found to transmit more light than the in situ nanocomposites. The glass transition temperature (T-g), decreased by similar to 16 degrees C for both the ex situ and in situ samples. Thermogravimetric analysis (TGA) indicated that the presence of Pd nanoclusters significantly improved the thermal stability of the nanocomposites, as evidenced by the enhanced onset of degradation by similar to 20 degrees C and similar to 40 degrees C for the in situ and ex situ nanocomposites, respectively. The electrical conductivity measurement shows a dramatic difference between these nanocomposites with a significantly higher value for the in situ nanocomposite (resistivity = 2.1 X 10(5) Omega m) compared to the ex situ nanocomposite (resistivity = 7.2 x 10(13) Omega m). (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: in situ and ex situ syntheses; Morphology; Nanocomposites